Three exposures to the spike protein of SARS-CoV-2 by either infection or vaccination elicit superior neutralizing immunity to all variants of concern - Wratil, Paul R.; Stern, Marcel; Priller, Alina; Willmann, Annika; Almanzar, Giovanni; Vogel, Emanuel; Feuerherd, Martin; Cheng, Cho Chin; Yazici, Sarah; Christa, Catharina; Jeske, Samuel; Lupoli, Gaia; et al. (Nature Medicine, 2022)
Infection-neutralizing antibody responses after SARS-CoV-2 infection or COVID-19 vaccination are an essential component of antiviral immunity. Antibody-mediated protection is challenged by the emergence of SARS-CoV-2 variants of concern (VoCs) with immune escape properties, such as omicron (B.1.1.529) that is rapidly spreading worldwide. Here, we report neutralizing antibody dynamics in a longitudinal cohort of COVID-19 convalescent and infection-naive individuals vaccinated with mRNA BNT162b2 by quantifying anti-SARS-CoV-2-spike antibodies and determining their avidity and neutralization capacity in serum. Using live-virus neutralization assays, we show that a superior infection-neutralizing capacity against all VoCs, including omicron, developed after either two vaccinations in convalescents or after a third vaccination or breakthrough infection of twice-vaccinated, naive individuals. These three consecutive spike antigen exposures resulted in an increasing neutralization capacity per anti-spike antibody unit and were paralleled by stepwise increases in antibody avidity. We conclude that an infection-plus-vaccination-induced hybrid immunity or a triple immunization can induce high-quality antibodies with superior neutralization capacity against VoCs, including omicron.
CRIS-Team Scopus Importer:2022-02-11